Sequence Characterization of Mitochondrial 12S rRNA Gene in Mouse Deer (Moschiola indica) for PCR-RFLP Based Species Identification. (23rd December 2013) - Siddappa, Chandra Mohan; Saini, Mohini; Das, Asit; Doreswamy, Ramesh; Sharma, Anil K.; Gupta, Praveen K.
Abstract : Mitochondrial 12S rRNA has proven to be a useful molecular marker for better conservation and management of the endangered species. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) of the mitochondrial 12S rRNA gene has proven to be a reliable and efficient tool for the identification of different Indian deer species of family cervidae. In the present study, mitochondrial 12S rRNA gene sequence of mouse deer ( Moschiola indica ) belonging to the family Tragulidae was characterized and analysed in silico for its use in species identification. Genomic DNA was isolated from the hair follicles and mitochondrial 12S rRNA gene was amplified using universal primers. PCR product was cloned and sequenced for the first time. The sequence of mouse deer showed 90.04, 90.08, 90.04, 91.2, 90.04, and 90.08% identities with sika deer, sambar, hog deer, musk deer, chital, and barking deer, respectively. Restriction mapping in Lasergene (DNAstar Inc., Madison, WI, USA) revealed that mouse deer mitochondrial 12S rRNA gene sequence can be differentiated from the other deer species in PCR-RFLP using Rsa I, Dde I, Bsr I, and Bst SFI. With the help of predicted pattern, mouse deer can be identified using genomic DNA from a variety of biomaterials, thereby providing molecular aid in wildlife forensics and conservation of the species.